Uma proposta para o ensino da noção de taxa de variação instantânea no ensino médio - Silva, Edson Rodrigues da (2012)
This work aims to lead students in the 3rd year of high school to construct meaning to the idea of instantaneous rate of change. With this intention, and based on the premises of Didactic Engineering, we elaborated, applied and analyzed a didactic sequence for eight students of a public school in the state of São Paulo. As theoric support, we used the Theory of Didactical Situation (TDS) and the Representation Theory of Semiotics Register. The TDS assisted us in development, tests and analysis of results of didactic sequence, while the Representation Theory of Semiotics Registers emphasized the diversity and articulation of different registers of representation in mathematical activities. The analysis of didactic sequence indicated that teaching students in the 3rd year of high school, through the simultaneous mobilization of records graphing, algebraic and tabular can construct meaning to the idea of rate of change